Perancangan Box Makanan Jinjing Berbahan Limbah Ampas Tebu dengan Pendekatan Ergonomi - Haryudiniarti, Ayu Nurul; Rochim, Irhas Luthfiansyah; Rivaldo, Muhamad; Maghrifah, Nurul; Ariyani, Ananda Putri; Irfan, Syahriza Badruzzaman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The increasing use of food boxes highlights the need for product designs that are not only functional but also ergonomic and environmentally friendly. This study aims to design a handheld food box made from sugarcane bagasse waste using an ergonomic approach. The research method applied ergonomic product design through user needs identification, questionnaire distribution, and hand anthropometric data collection. Anthropometric data were obtained from 31 Industrial Engineering students of Universitas Global Jakarta, including maximum grip diameter, maximum palm width, palm thickness, and four-finger breadth. The data were tested for normality and processed using percentile values as the basis for determining design dimensions. The results indicate that the application of anthropometric data produces a handheld food box design that is more comfortable, stable, and suitable for user characteristics. In addition, the utilization of sugarcane bagasse waste shows potential as an environmentally friendly and sustainable alternative material.